ABD: A machine intelligent-based algal bloom detector for remote sensing images[Formula presented] - Ananias, Pedro Henrique M. [UNESP]; Negri, Rogério G. [UNESP]; Bressane, Adriano [UNESP]; Colnago, Marilaine [UNESP]; Casaca, Wallace [UNESP] (Elsevier, 2023)
This paper presents a new approach for detecting algal insurgence in water environments by using remote sensing image series. The designed methodology provides a robust and accurate algorithm as an alternative to typical algal bloom detection methods. In more technical terms, by only assuming as input an image time series, a fully automatic data-driven scheme involving pre-processing and feature extraction procedures is derived, which models a machine intelligent-based classifier capable of detecting algal blooms. Lastly, algal insurgence maps are then produced by passing to the classifier an image taken at an instant of interest.
Keywords: Algal bloom; Machine learning; Remote sensing; Spectral index